WORKSHOP FINANCIAL LIFE SKILLS DALAM UPAYA PENINGKATAN LITERASI KEUANGAN REMAJA DI JAWA BARAT - Deti, Regina; Septina , Nina; Danil, Lilian; Iskandarsyah, Triyana; Intanie, Vera; Barlian, Inge (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M), 2024)
This dedication to the community is aimed at equipping high school/SME students with an adequate understanding of the financial life skills that will be useful for high school students in the world of work that will enter soon after graduation. The training will be conducted online through five online modules that cover critical thinking in decision-making, budgeting and financial management, positive communication, overcoming the habit of delaying work and being responsible. This module was developed by the USAID YEP program, which will be a partner of community dedication activities. The workshop was held 8 times with a total of 138 youth participants. This dedication to the community provides only five materials so that it opens up opportunities for other activities to provide other materials.